Peningkatan Hasil Belajar Siswa Pada Keterampilan Menulis Muatan Pelajaran Bahasa Indonesia Menggunakan Media Pembelajaran Kartu Kilas (Flash Cards) - Sulistiyowati, Ami (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The aim of this research is to determine the improvement of students ‘learning outcomes in writing skill of indonesian by using flash cards media. The research conducted was a Classroom Action Research (PTK) with three cycles consisting of two meetings. Each meeting is carried out a pre test and post test. The subjects of this study were grade I SD Negeri Banjaranyar 01 which consisted of 24 students. KKM standard 65 out of 24 students only 11 students or 45.8% who reached a value of 65 and above while 13 students or 54.2% got a score below KKM. The results showed that the improvement of students”learning outcomes in writing skills of  Indonesian. In the pre-cycle obtained an average score of the 45.8%. Then increased in first cycle with a score of 58.3%, increased back in the second cycle 87.5%. These results indicated that using flash cards can improved the sudents”learning outcomes in writing skills of Indonesian especially grade I at SD Negeri Banjaranyar 01 Brebes.